The STEAM learning performance and sustainable inquiry behavior of college students in China - Nong, Liying; Liao, Chen; Ye, Jian-Hong; Wei, Changwu; Zhao, Chaiyu; Nong, Weiguaju (Frontiers in Psychology, 2022)
Teacher education students, as an important reserve in the field of education, their growth and development are related to the future of science, economy, sustainable development of education. Through participation in the educational practice of STEAM, which integrates science, technology, engineering, art, and mathematics is more beneficial for them to acquire 21st century skills like communication, collaboration, learning innovation and critical thinking. However, little has been seen about the use and effectiveness of short videos in STEAM education activities and how they can be used to support and promote teacher education students STEAM learning performance and sustainable inquiry behaviors. Therefore, this study combines the framework of triadic reciprocity determinism theory and technology acceptance theory to propose six research hypotheses and develop a research model to explore the relationship between collaborative self-efficacy (CS-E), perceived usefulness (PU) of short videos, perceived ease of use (PEOU), STEAM learning performance and teacher education students’ sustainable inquiry behavior. To achieve the purpose of this study, this study used purposive sampling and invited teacher education students from five classes of preschool education at a university in Guangxi Zhuang Autonomous Region (GZAR), China, to participate in this study. A total of 8 hours of instructional guidance was provided over a four-week period, in which participants used short videos for collaborative group learning and independent inquiry and applied STEAM concepts to kindergarten science activities. Participants’ STEAM performance was measured and surveyed during the fourth week. The results of the study validation showed that (1) teacher education students CS-E had a positive effect on the PU and PEOU of short videos; (2) Teacher’s education students PEOU of short videos had a positive effect on usefulness; (3) Teacher’s education students PU and PEOU of short videos had a positive effect on STEAM learning performance; (4) Teacher’s education students’ STEAM learning performance had a positive effect on sustainable inquiry behavior.